Gibberellic acid (GA3) can shorten the grafting cycle through enhanced seedling growth and biomass in cashew (Anacardium occidentale L.) - ,, Lakshmipathi; Adiga, J. D.; Kalaivanan, D. (Journal of Plantation Crops, 2020)
Due to the slow growth of cashew seedlings, nurserymen and growers have to wait for more time for taking up softwood grafting operations to market or planting them. The use of growth regulators has resulted in a shortening of propagation time in many fruit crops. Therefore, the nursery experiment was conducted to study the effect of foliar spray of GA3 and NAA on the growth and biomass of cashew seedlings. Five treatments viz., control and foliar application of GA3 @ 50 ppm, GA3 @ 100 ppm, NAA @ 50 ppm and NAA 100 ppm were replicated four times in completely randomized design. Growth regulators were sprayed on 10 days old seedlings of cashew cultivar Vengurla-4. Cashew seedlings sprayed with GA3 @ 100 ppm recorded highest shoot length, seedling length and girth, leaf numbers, shoot fresh weight and shoot dry weight. However, spraying of NAA @ 100 ppm recorded maximum root length and highest root fresh weight and root dry weight. Irrespective of the treatments, most of the seedling growth parameters increased as days progressed. Post germination sprays with GA3 @ 100 ppm can be effectively employed for increasing the seedling growth of cashew which would help in producing healthy seedlings in a short period for advancing the grafting operations and in turn reduce the duration of propagation as well as the cost of seedling production.